Namuzaj Ta’allum CIRC (Al-Qira’ah Al-Ta’awuniyah Al-Mutakamilah wa Al-Ta'awuniyyah) fiTa’lim Maharah Al- Qira’ah - Rahmawati, Rahmawati; Qibtiyah, Luthfatul (STAI Syaichona Moh. Cholil Bangkalan, 2024)
This research aims to determine the implementation of the CIRC (Cooperative Integrated Reading and Composition) learning model and supporting and inhibiting factors for implementing the CIRC (Cooperative Integrated Reading and Composition) learning model in teaching reading skills for class X female students. This research uses a qualitative approach with a descriptive type. This research was conducted at MA Al-Amien 1 Pragaan. The data collection techniques used were observation and interviews. The subjects of this research were taken from teachers and students. Data analysis used the Saldana, Miles, and Huberman models, which consist of condensation data, data presentation, and conclusions. For data validity, researchers used source triangulation. The results of this research are: 1. Implementation of the CIRC (Cooperative Integrated Reading and Composition) Learning Model in Reading Skills Learning, namely: a. Preparation stage. Create initial conditions for students. Then, ask questions related to the previous lesson. b. The implementation stage includes Forming heterogeneous groups of around 4 people. The teacher gives a discourse or clipping according to the material to be studied, and students work together to read to each other, find the main idea, respond to the discourse or clipping written on a piece of paper, and present/read out the results group. c. Evaluation stage. Female students do exercises related to the qira'ah text in book 2. Supporting and inhibiting factors for implementing the CIRC (Cooperative Integrated Reading and Composition) Learning Model in Learning Reading Skills: a. class facilities, b. students' abilities.